PWE-125 What happens after stenting an oesophageal cancer? the need for repeat interventions. (17th June 2017) - Corrigall, D; Gooding, I
Abstract : Introduction: Oesophageal stents are standard treatment for obstruction secondary to malignancy. Published data indicated successful relief of dysphagia in over 90% of patients (1), with a complication rate of between 30%–50% (2). However, there is less published experience on the need for re-intervention after index stent insertion. We aimed to look at the frequency, causes, and treatment of stent failure. Method: We performed a retrospective search of the endoscopy database to identify all oesophageal stents placed from January 2008 to July 2016 and all subsequent gastroscopies for these patients. At each procedure, we extracted (1) indication (2) findings (3) intervention performed and (4) survival or time to next OGD. A need for a further gastroscopy was used as a proxy for stent failure. We performed Kaplan Meier (KM) analysis to compare treatments. Results: 300 oesophageal stents were placed, of which 214 were for malignancy. 104 (48.6%) of these patients received a second endoscopy at a median time of 42.9 days. 56 (53.8%) had a third endoscopy and 25 then had a further endoscopy. 7 patients had 6 or more endoscopies with one patient having 9 procedures. There were a total of 237 repeat gastroscopies. Caused of recurrent dysphagia were food bolus obstruction of the stent (30 occurrences), stent migration (12), tumour overgrowth of the proximal (23) or distal (5) ends of the stent, tumour ingrowth through the stent walls (82), a peptic stricture above the stent (7), a stricture due to radiotherapy (3) or the distal end of the stent impacting on the greater curve (6). There were 6 tracheo/broncho-oesophageal fistulae and 19 cases of bleeding from a tumour that had been stented. On 38 occasions (16%) the stent was in situ and patent and no cause for dysphagia was found. Combining the cases of tumour overgrowth and ingrowth, this was treated with argon plasma co-agulation (APC; 55 procedures), balloon dilatation (9), APC and balloon dilatation (5), restenting (15) or a nasogastric tube (3). KM analysis shows that while cases that were re-stented required later re-intervention, this difference is not significant. Conclusion: Oesophageal stents placed to relieve malignant dysphagia commonly require re-intervention. Frequently (16%) the symptoms are not caused by a failure of the stent and therefore have a non-mechanical cause. Growth of the tumour, in particular ingrowth of the stent, is the commonest cause of recurrent dysphagia (46%). We did not detect a significant difference between APC, re-stenting and dilatation as treatment. References: . Guidelines for the management of oesophageal and gastric cancer. Allum, et al. Gut2002;50(Suppl V):v1–v23 . Role of Esophageal Stents in Benign and Malignant Diseases. Sharma, et al. Am J Gastroenterol2010; 105:258–273 Disclosure of Interest: None Declared